Artificial intelligence plus molecular profiling for personalized radiotherapy: Questions 105–107 in the 150 most important questions in cancer research and clinical oncology series - Song Ting; Li Huali (Visualized Cancer Medicine)
Artificial intelligence (AI) has been increasingly applied in cancer prevention, diagnosis, prognosis, treatment planning, and therapy implications. For enhancing professional communication and promoting research collaboration, Visualized Cancer Medicine continues the program of publishing the 150 most important questions in cancer research and clinical oncology. In this article, we propose three new key questions about integrating AI into radiation therapy for cancer patients as follows. Question 105: How can we develop individualized radiation therapy based on the biological variations combined with AI analysis for better treatment outcomes and less treatment toxicity? Question 106: Can AI improve real-time dose monitoring and adjustments in radiotherapy? Question 107: Can molecular profiling plus AI be help predict the benefits of adjusting the plan in adaptive radiotherapy?